Gereja, Gawai, dan Generasi Z: Pemuridan Iman sebagai Solusi Pencegahan Pornografi pada Remaja Kristen - Purba, Novia Cristina (Sekolah Tinggi Teologi Torsina Surakarta, 2023)
Generation Z, as digital natives, faces serious challenges from massive exposure to pornography through digital spaces, which has destructive impacts on the psychological, relational, and spiritual dimensions of Christian adolescents. Previous studies have tended to address pornography, digital discipleship, and Gen Z spirituality separately, resulting in the absence of a holistic, integrative framework. This article aims to formulate a conceptual framework of faith discipleship relevant to Christian Gen Z adolescents as a preventive strategy against pornography involvement. This research employs a literature review method with a theological-practical approach. The findings reveal three main points: first, understanding the digital spirituality landscape of Gen Z serves as an essential foundation; second, pornography must be read as a spiritual crisis, not merely a moral issue; third, the reconstruction of faith discipleship based on relationships, accountability, and the integration of Christian sexuality education becomes a strategic solution. Church, family, and Christian schools must synergize in building a holistic digital discipleship ecosystem so that gadgets become a means of Christ's presence for Generation Z. Abstrak Generasi Z sebagai digital natives menghadapi tantangan serius berupa paparan pornografi yang masif melalui ruang digital, yang berdampak destruktif terhadap dimensi psikologis, relasional, dan spiritual remaja Kristen. Penelitian-penelitian terdahulu cenderung membahas isu pornografi, pemuridan digital, dan spiritualitas Gen Z secara terpisah, sehingga belum tersedia kerangka integratif yang holistik. Artikel ini bertujuan merumuskan kerangka konseptual pemuridan iman yang relevan bagi remaja Kristen Gen Z sebagai strategi pencegahan keterlibatan dalam pornografi. Penelitian ini menggunakan metode kajian pustaka dengan pendekatan teologis-praktis. Hasil penelitian menunjukkan tiga temuan utama: pertama, pemahaman terhadap lanskap spiritualitas digital Gen Z menjadi fondasi penting; kedua, pornografi harus dibaca sebagai krisis spiritualitas, bukan sekadar isu moral; ketiga, rekonstruksi pemuridan iman berbasis relasi, akuntabilitas, dan integrasi pendidikan seksualitas Kristen menjadi solusi strategis. Gereja, keluarga, dan sekolah Kristen perlu bersinergi membangun ekosistem pemuridan digital yang holistik agar gawai menjadi sarana kehadiran Kristus bagi Generasi Z.